ANALISIS ANTRIAN PADA “SUPERMARKET COOL” TOMOHON MENGGUNAKAN TEORI ANTRIAN UNTUK MENENTUKAN PELAYANAN YANG OPTIMAL - Imelda Christina Bella Chandra Chan; Marline Sofiana Paendong; Tohap Manurung (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2023)
IMELDA CHRISTINA BELLA CHANDRA CHAN. Queuing Analysis on “Supermarket Cool” Tomohon by using queuing theory in determining optimal service. Under the guidance of MARLINE S. PAENDONG as the head of the team and TOHAP MANURUNG as the member. The fulfillment of customer demands in both levels of quantity and quality has caused the business world to continue striving in improving their service quality. A company that provides slow service will cause longer queues. Thus, the researcher tried to evaluate cashier service for 7 days. This study aims to determine queuing model, the average amount of customer visit, average service of the supermarket, and optimization of the cashier service quantity. The analysis method that has been implied for this study is direct observation and used descriptive analysis and multiple lane queuing model that has more than one service facility or queuing structure that has been applied at the supermarket which is multi-channel single phase. The result of the study showed that “Supermarket Cool” Tomohon there was a long queue at the noon around 11 am to 1 pm. This result was obtained by using multiple lane queuing model. There were 4 customers who had been waiting for 8 to 9 minutes, and there were 2 customers in the system that spent 4.638 minutes. In addition, during the evening service time, there were 3 customers in the line and spent 6-7 minutes for the payment transaction. This happened around 6 pm to 8 pm, meanwhile there were 2 customers in the system who spent 3 to 4 minutes. The results showed that by adding 2 cashier facilities during the peak hours shortened the queuing line.